Measuring Faculty Engagement in Online Formative or Whole-Person Education: A Revised Instrument and Item Response Theory Model - Wortham, Stanton; Borowiec, Katrina; Kim, Deoksoon (Online Learning, 2023)
The COVID-19 pandemic reinforced the importance of supporting students’ comprehensive well-being when teaching online. One promising approach is formative or whole-person education, which emphasizes wholeness, purpose, and community. We created a scale using a polytomous Item Response Theory modeling approach, measuring the extent to which postsecondary teachers engage in formative education online. To our knowledge, this is the first scale designed to measure this construct. The scale was developed within an exploratory sequential mixed methods study on formative education online that also included semi-structured interviews with 37 faculty members. Results from the qualitative analysis were used to develop initial items. This data-informed process increased the construct validity of the scale. We refined the original item pool through a pilot test using a sample of 308 instructors. This article presents psychometric results for the final, 10-item scale using a sample of 245 instructors. Evaluation of item fit statistics, item trace lines, and the total information curve indicate that the graded response model was appropriate for this scale. The Cronbach’s alpha and marginal reliability coefficients for the final scale were .90 and .91, indicating good reliability. Future research can explore how this scale might be adapted for in-person learning environments and other contexts.